The influence of cyber culture on students' digital literacy - Desiany, Mia; Komalasari, Kokom; Anggraini, Diana Noor (JIPSINDO, 2024)
The study aims to analyze the influence of cyberculture on digital literacy skills in the context of social studies learning. Adopting a quantitative research design, the study employs a correlational approach and utilizes various data collection methods, including observation, document review, and questionnaires. The research was conducted at SMP Negeri 50 Bandung, where 1,169 students were surveyed in grades seven, eight, and nine. The sample was determined using the proportional stratified random sampling technique, resulting in a sample size of 300 students. The data analysis technique employed is a simple linear regression analysis test. The study's findings indicated that cyberculture in social studies learning significantly affected the literacy skills of students at SMP Negeri 50 Bandung, with a variable correlation level in the medium category.